Perceiving affordances and the problem of visually indiscernible kinds - Hansen, Mette Kristine (Frontiers in Psychology, 2024)
In this study, I defend the claim that we can perceptually experience what objects afford when we engage with objects belonging to natural or artificial categorical high-level kinds. Experiencing affordances perceptually positions us to act in specific ways. The main aim of this study was to argue that this view has explanatory advantages over alternative views. An increasingly popular view within the philosophy of perception, most famously defended by Susanna Siegel, claims that we sometimes visually experience natural and artificial objects as belonging to categorical high-level kinds. When visually experiencing a lemon, one does not only experience its low-level properties such as shape and color, sometimes one also experiences the object as a lemon. A challenge arises when attempting to explain what happens when one experiences an object that is experientially indistinguishable from another object, yet these objects belong to different high-level categorical kinds. For instance, if someone perceptually experiences a lemon as a lemon, her experience can be considered as accurately representing or presenting a lemon. However, if the subject perceptually experiences a lemon-shaped soap bar, which cannot be discriminated from a real lemon by sight alone, the experience is deemed inaccurate because there is no real lemon present. The problem is that such a judgment seems counterintuitive; unlike with hallucinations and illusions, there seems to be nothing wrong with how the object appears. Therefore, it is difficult to understand how the mistake could be a perceptual mistake. I will first present arguments supporting the claim that when we visually encounter objects such as lemons, we sometimes also perceive the affordances of these objects—what they provide or offer us. I will further argue that this perspective on affordances offers a more compelling explanation than other alternative accounts when it comes to our perception of visually indistinguishable objects that nonetheless belong to categorically distinct high-level kinds.